Automated FRET quantification shows distinct subcellular ERK activation kinetics in response to graded EGFR signaling in Drosophila. (16th April 2019) - Ogura, Yosuke; Sami, Mustafa M.; Wada, Housei; Hayashi, Shigeo
Abstract: Threshold responses to an activity gradient allow a single signaling pathway to yield multiple outcomes. Extracellular signal‐regulated kinase (ERK) is one such signal, which couples receptor tyrosine kinase signaling with multiple cellular responses in various developmental processes. Recent advances in the development of fluorescent biosensors for live imaging have enabled the signaling activities accompanying embryonic development to be monitored in real time. Here, we used an automated computational program to quantify the signals of a fluorescence resonance energy transfer (FRET) reporter for activated ERK, and we used this system to monitor the spatio‐temporal dynamics of ERK during neuroectoderm patterning in Drosophila embryos. We found that the cytoplasmic and nuclear ERK activity gradients show distinct kinetics in response to epidermal growth factor receptor activation. The ERK activation patterns implied that the cytoplasmic ERK activity is modulated into a threshold response in the nucleus. Abstract : Fluorescence resonance energy transfer (FRET) imaging of cytoplasmic extracellular signal‐regulated kinase (ERK) activity in the Drosophila embryo. A. Time course of FRET imaging. B. Temporal change of ERK activity gradient along the DV axis measured in for quadrants along the AP axis.